Analysis of Olympic Games (Rio de Janeiro, 2016) participants' individual competition compositions in calisthenics - Y.O. Kovalenko; V.N. Boloban (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
Purpose: to show structural elements of individual competition compositions of female gymnasts - Olympic Games (Rio de Janeiro, 2016) finalists. Material: video-computer analysis of Olympic Games participants' exercises; analysis of competition records. Results: it was found that female gymnasts' individual fitness is characterized by the following: correlation of time for Body Difficulty elements' fulfillment and Apparatus Difficulty elements. It is expressed in quickness of preparation to element's fulfillment; in logical and technically accurate transition from element to element. Accent on static elements permitted for sportswomen to reduce movements' area. With dynamic style of elements' fulfillment movements' area was larger. Conclusions: Most female gymnasts demonstrated natural elements' distribution in compositions. Space movements opened the best views of static and dynamic elements' fulfillment that was an evidence of female gymnasts' high sportsmanship.